COMBINED HORMONOTHERAPY WITH GNRG ANALOGUE AND INTRAUTERINE LEVONORGESTREL-RELEASING SYSTEM OF ATYPICAL ENDOMETRIAL HYPERPLASIA AND WELL-DIFFERENTIATED ENDOMETRIAL CARCINOMA: PROSPECTIV PILOT RESEARCH - A. I. Pashov; V. B. Tskhai; E. N. Sivova (Acta Biomedica Scientifica)
The article presents the results of organ-preserving treatment protocol of atypical endometrial hyperplasia and well-differentiated endometrial carcinoma in young women. This protocol was applied in 24 patients. The period of patients observation was 3—6 years. During 6—9 months the patients were given GnRG analogue with add-back therapy. Intrauterine levonorgestrel-releasing system was inserted with therapeutic purpose for the period of not less than 6 months in atypical endometrial hyperplasia and for 1 year for well differentiated endometrial carcinoma. Combined using of GnRG analogue and intrauterine levonorgestrel-releasing system is effective method for treatment of atypicalendometrial hyperplasia and endometrial carcinoma stage I А in young women, especially in cases of unrealized fertility and can be considered as an alternative way to hysterectomy.